Penerapan Milik Run System Berbasis Lean Logistics untuk Efisiensi Distribusi dengan Metode VRP - Alvariedz, Ridwan Salman; Berman, Ega Taqwali; Larutama, Wiku (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Supplier X in Lembang faces distribution efficiency issues due to a conventional delivery system that results in long travel distances and high operational costs. This study aims to optimize the distribution system through the implementation of a Milk Run System based on Lean Logistics and the Vehicle Routing Problem (VRP) method using the Nearest Neighbor algorithm. This case study involves the delivery of cabbage to five local markets with a total demand of 1,000 kg using a single pick-up vehicle. The analysis stages include data identification, distance matrix development, savings calculation, and route simulation. The results show a reduction in travel distance from 101.8 km to 41.3 km, travel time to 99.12 minutes, and distribution cost efficiency from Rp326,800 to Rp267,700 per day. This study recommends the implementation of an integrated lean-based distribution system as a strategy to enhance logistics efficiency and operational sustainability.